Boas práticas em gestão de riscos como contribuições ao plano de integridade da UFSM: um olhar à luz dos diretores das unidades de ensino - Borges, Josiane dos Santos Souza (2023)
The general objective of this work is to propose good risk control and management practices, from the perspective of unit directors, aiming to contribute to the UFSM Integrity Plan. To achieve this objective, descriptive research was carried out, of a qualitative nature and in relation to the research strategy, the study is configured as a case study whose object of analysis was the Federal University of Santa Maria, a public Federal Higher Education Institution. . Data collection occurred through semi-structured interviews and documentary research. The interviews were carried out with 12 (twelve) UFSM employees who hold management positions in the Education Units. Based on the results, it can be inferred that the biggest difficulties highlighted by the interviewees refer to the risks of legal compliance and image and reputation. On the other hand, the greatest facilities highlighted were in relation to operational and financial/budgetary risks. The results pointed to the managers' conceptions for dealing with demands that can be configured as risks, when presented in their work routines, however they are still individualized and sparse, not institutionalized. Based on the reflections of the interviewees, the present study resulted in the preparation of a Digital Booklet on good risk management practices, which will be public and made available on the UFSM website, specifically in the Sector Corregedoria.